An Analysis of Violations of Maxims’ Cooperative Principle in Creating Humor in American Situation Comedy ‘Friends’ - Marsheila, Michelle Aulia; Apriliyanti, Dewi Listia (PROJECT (Professional Journal of English Education), 2025)
Cooperative maxim principles refer to the rules that should be obeyed to generate effective and efficient communication in a conversation. However, in certain circumstances, cooperative maxim violation may create a sense of humor among audiences. Hence, this study is conducted to analyze the violation of four maxims in cooperative principles to create humor in one of the episodes of the American situation comedy ‘friends’ (Episode 9 in 6th Season: “The One When Ross Got High”). Grice’s four maxims; Quality, Quantity, Relation, and Manner are the main analysis tool in the study. This research is conducted by using a descriptive qualitative study. The primary data is taken from the video of the sitcom and the dialogue was transcribed. The result revealed that there were 27 maxim violations; 13 times quality maxim violation, two times quantity maxim violation, three times relation maxim violation, and 9 times manner maxim violation. The ‘friends’ sitcom characters are dishonest, provide unnecessary details, are redundant, and cause expression obscurity and ambiguity. However, these violations, in the eyes of sitcom viewers, attract laughter and a humorous effect.